Challenges of International Criminal Law: Gender and Global Justice Perspectives. Book Review: Gender and International Criminal Law by Indira Rosenthal et al. (2022) - Madrigal-Vargas, Valeria (2024)
The International Criminal Law (IPL) has become a significant tool in the international system, not only to contribute to the maintenance of order, but also as a means of assigning responsibilities to States that violate international norms. As a branch of law, it is grounded in a long-standing and evolving transcendence that seeks to adapt to global realities. More recently, the relevance of the gender perspective within IPR and how it can be perspective within IPR and how it can bring about a radical change in the way in which in the way in which States have perceived IPR up to the present time. Along the same lines, the book Gender and International Criminal Law, edited by Indira Rosenthal edited by Indira Rosenthal, Valerie Oosterveld and Susana SáCouto (2022) comes to question the established dynamics within the question the dynamics established within International Criminal Law, which, according to the authors that, according to the authors, exclude and violate populations during the implementation of legal frameworks. implementation of legal frameworks.